Pengaruh Kualitas Produk, Kualitasipelayanan Dan Harga Terhadap Loyalitas Pelanggan Pada Mie Gacoan Cabang Jember - Farida Umi Choiriyah; Ashilah, Khittah; Frastiyo, Wahyu Frastiyo (LAN TABUR : Jurnal Ekonomi Syariah, 2025)
Mie Gacoan is the first food outlet in Indonesia to serve a noodle menu with a spicy level that can be adjusted. One of its branches is in the city of Jember which has received a positive response from the community, where since the grand opening until now it is always crowded with customers. The purpose of this study is to test and analyze partially and simultaneously the effect of product quality, service quality and price on customer loyalty. The method used is descriptive quantitative, with ex post facto research type. The population in this study is an unlimited number of Mie Gacoan Jember customers and a sample of 150 loyal respondents, namely with the criteria of having bought Mie Gacoan products more than twice. The data collection techniques used are observation and questionnaires. The data obtained were then analyzed using multiple linear regression techniques. The results of this study show that partially product quality has a positive and significant effect on customer loyalty, service quality has no effect on customer loyalty and price has a positive and significant effect on customer loyalty. The test simultaneously obtained the results of product quality, service quality and price simultaneously had a positive and significant effect on customer loyalty with a contribution of 37%. Keywords: product quality, service quality, price, customer loyalty